Review of the application of drones for smart cities - Hana Důbravová; Vladimír Bureš; Lukáš Velfl (IET Smart Cities)
Abstract In an area of increasing digitalisation and rapid technological development, information management is becoming essential for the effective functioning of modern organisations and cities. One of the new trends is the gradual expansion and use of drones in parts of the smart cities concept. In security, drones are used to protect public order, monitor traffic in cities and municipalities, and control sub‐activities falling under the competence of police forces. In rescue work, drones allow us to efficiently and quickly manage accidental emergencies in hard‐to‐reach areas. At the same time, in the transport sector, drones have become an important component for the efficient delivery of parcels, reducing overall costs and time savings. This paper systematically overviews the importance of drones in various fields such as security, transportation, rescue operations or parcel delivery. Drones are becoming key elements for public order, crisis management and enhancing the quality of life of citizens in smart cities due to their capabilities of rapid response, monitoring hard‐to‐reach locations and autonomous data collection. Particular attention is then paid to comparing the use of drones in the Czech Republic and abroad and their benefits in the field of innovative technologies that help improve the safety and efficiency of urban services. The article also analyses the technical specifications of drones and their role in the public and private sectors, considering the legislative framework for their use. Overall, the article offers an overview of how drones contribute to integrating modern technologies into the daily functioning of smart cities and improving residents' quality of life.